Effect of a flavoring component on water consumption and performance of piglets during nursery (Research, Society and Development, 2023)
The study assessed the addition of a commercial flavoring agent in the water used for piglets on water consumption and performance during the post-weaning period. The study used 60 piglets distributed in a randomized block experimental design, which included two treatments: with and without the inclusion of a commercial flavoring agent: 100 g/1000L with ten replications per treatment, each replication using three animals. The calculated parameters were: mean water consumption per animal, total daily water consumption, mean daily feed consumption, total feed consumption, mean feed consumption, daily weight gain, mean daily weight gain, total weight gain, feed conversion, feed efficiency, and diarrhea occurrence. The flavoring agent inclusion increased the mean water consumption per animal and the total daily water consumption in phase one and two of the experiment. However, the inclusion did not significantly influence the mean feed daily consumption, total feed consumption, and daily weight gain. There was a positive correlation between water and feed consumption for both treatments in the first phase, with a higher mean for the flavoring agent treatment group's initial feed/water consumption rate. The analysis of the entire cycle did not display statistical differences between the groups for the studied variables. In addition, the diarrhea occurrence did not differ between treatments. The results of this experiment indicate that manipulating the hedonic characteristics of drinking water by adding the flavoring agent is beneficial with regard to increasing water consumption in the first two weeks after weaning.